Current and future uses of IT in Europe and the Far East: Achieving competitive advantage with 3PL - Hosie, Peter; Lim, M.; Tan, A.; Yu, Y. (Inderscience Publishers, 2012)
Current and future IT applications effecting supply chains in Europe and Pacific Asia are investigated. 3PL providers increasingly use IT systems for logistics, to enhance supply chain collaboration with business partners. Advanced systems are not always immediately profi table. Most companies already implement IT systems for processing transactions but motivations vary and barriers remain since 3PL providers incompletely understand clients’ IT requirements. Long-term productivity gains require sophisticated IT systems to streamline cycles and improve supply chain visibility to facilitate, plan and make decisions. RFID and advanced integration systems, including Business Process Management, are probably the next trend in IT logistics systems.